Depletion of the Microbiota Has a Modest but Important Impact on the Fungal Burden of the Heart and Lungs during Early Systemic Candida auris Infection in Neutropenic Mice - Amber M. Pichowicz; Steven R. Torres; Fernando J. Torres-Velez; Adina D. Longyear; Navjot Singh; Erica Lasek-Nesselquist; Magdia De Jesus (Microorganisms, 2022)
The progression and systemic pathobiology of C. auris in the absence of a microbiota have not been described. Here, we describe the influence of the microbiota during the first 5 days of C. auris infection in germ-free or antibiotic-depleted mice. Depletion of the bacterial microbiota in both germ-free and antibiotic-depleted models results in a modest but important increase in the early stages of C. auris infection. Particularly the heart and lungs, followed by the cecum, uterus, and stomach, of intravenously (i.v.) infected neutropenic mice showed significant fungal organ burden. Understanding disease progression and pathobiology of C. auris in individuals with a depleted microbiota could potentially help in the development of care protocols that incorporate supplementation or restoration of the microbiota before invasive procedures, such as transplantation surgeries.